Immunohistochemical Femoral Nerve Study Following Bisphosphonates Administration - Vasileios Alexandros Karakousis; Danai Liouliou; Aikaterini Loula; Nikoleta Kagianni; Eva-Maria Dietrich; Soultana Meditskou; Antonia Sioga; Theodora Papamitsou (Medicina, 2020)
Background and objectives: Bisphosphonates represent selective inhibitors of excess osteoblastic bone resorption that characterizes all osteopathies, targeting osteoclasts and their precursors. Their long-term administration in postmenopausal women suffering from osteoporosis has resulted in neural adverse effects. The current study focuses on the research of possible alterations in the femoral nerve, caused by bisphosphonates. We hypothesized that bisphosphonates, taken orally (per os), may produce degenerative changes to the femoral nerve, affecting lower-limb posture and walking neuronal commands. Materials and Methods: In order to support our hypothesis, femoral nerve specimens were extracted from ten female 12-month-old Wistar rats given 0.05 milligrams (mg) per kilogram (kg) of body weight (b.w.) per week alendronate per os for 13 weeks and from ten female 12-month-old Wistar rats given normal saline that were used as a control group. Specimens were studied using immunohistochemistry for selected antibodies NeuN (Neuronal Nuclear Protein), a protein located within mature, postmitotic neural nucleus, and cytosol and Sox10 (Sex-determining Region Y (SRY)—High-Motility Group (HMG)—box 10). The latter marker is fundamental for myelination of peripheral nerves. Obtained slides were examined under a light microscope. Results: Samples extracted from rats given alendronate were more Sox10 positive compared to samples of the control group, where the marker’s expression was not so intense. Both groups were equally NeuN positive. Our results are in agreement with previous studies conducted under a transmission electron microscope. Conclusions: The suggested pathophysiological mechanism linked to histological alterations described above is possibly related to toxic drug effects on Schwann and neuronal cells. Our hypothesis enhances the existing scientific evidence of degenerative changes present on femoral nerve following bisphosphonates administration, indicating a possible relationship between alendronate use and neuronal function.